Politeness Strategies Used in Mata Natjwa Program; Cipta kerja: Mana Fakta Mana Dusta - Veronika Anggun Indahsari; Ribut Surjowati (STKIP PGRI Tulungagung, 2021)
This paper is aimed at analyzing the types of Politeness strategies used by the host of Mata Natjwa when she makes an interview with the guest stars. This study is interesting to be done because it reveals whether the power relations between the host and the guests influence the use of the politeness strategies. The study is descriptive qualitative study in which all the data were analyzed described based on the theory proposed by Brown and Levinson (1987). There data were taken from the MN episodes whose topic is Cipta kerja: Mana Fakta Mana Dusta. After the data were collected, and reduced, they were classified based on the classification in Brown and Levinson (1987) theory. The analysis started by classifying the types of PS and then they were divided again into subdivision of types of Politeness strategies. In order to make the analysis more clearly, those data were displayed. The findings show that Natjwa used positive politeness with the type of seeking agreement, asserting of presuppose S’s knowledge of and concern for H’s want, avoiding agreement, using in group identity marker, and including both speaker and hearer to the activity. The types of negative politeness and bald on strategy are not as many as that found in positive politeness, namely; minimizing imposition on the other person, and questioning and hedging., meanwhile the last type of PS is tasking oriented which belong to bald on record strategies.